Advancement in Sclerotinia rot management in Indian mustard (Brassica juncea L.): Advancement in Sclerotinia rot management in Indian mustard (Brassica juncea L.) - PANKAJ SHARMA; P D MEENA; V V SINGH; N C GUPTA; H K SHARMA; P K RAI (Journal of Oilseeds Research, 2020)
Sclerotinia sclerotiorum is one of the important a fungal plant pathogens affecting all Brassica oilseed species grown in India. Management of the disease by crop rotation has limited success due to the pathogen’s wide host range and long-term survival as resting bodies (sclerotia) in the soil. Nine B. juncea lines showing low levels of disease have been identified. Two of these lines were crossed with high yielding B. juncea varieties and further work on mapping quantitative trait loci (QTL) conferring resistance to Sclerotinia using populations of recombinant inbred lines (RIL) derived from the two crosses is under progress.